Cardiovascular and osteoporosis protection at menopause with lycopene: A placebo-controlled double-blind randomized clinical trial - Meeta Meeta; Sudhaa Sharma; Jyothi Unni; Sunila Khandelwal; Ambuja Choranur; Sonia Malik (Wolters Kluwer Medknow Publications, 2022)
Objective: The effect of lycopene (LycoRed) supplementation was evaluated in healthy postmenopausal women by biochemical markers for cardiovascular protection and osteoporosis protection. Study Settings and Design: This was a multi-centric placebo-controlled double-blind randomized clinical trial that screened 198 postmenopausal women at 21 centers across 12 cities in India. Levels of lycopene, lipid profile, high-risk C-reactive protein, and bone turnover markers: amino-terminal propeptide of Type I collagen (P1NP) and C-terminal telopeptide of Type I collagen (β-CTx) were measured at baseline and 6 months postsupplementation with LycoRed or placebo. Interventions: The study was completed with 57 of the 100 women on LycoRed 8 mg (antioxidant potency is equivalent to 24 mg of lycopene) and 43 placebos for 6 months by randomization. Main Outcome Measures: Rise in serum lycopene and effect of serum lycopene on surrogate markers of cardiovascular health and bone health. Results: LycoRed supplementation increases lycopene levels and P1NP and nonsignificant fall in β-CTx levels in healthy postmenopausal women. Conclusions: Lycopene supplementation in Indian menopausal women may confer protection from osteoporosis as shown by the directional change in the surrogate biochemical markers. This study can form a basis for larger studies with different doses to understand the effect of lycopene to prevent and act as adjuvant treatment on clinical endpoints for cardiovascular disease (CVD) and bone health.